Pengaruh Jenis Pupuk Daun Terhadap Pertumbuhan Vegetatif Tanaman Anggrek Cattleya sp - rianda, mayu arya; listiawati, agustina; Budi, Setia (Jurnal Sains Pertanian Equator, 2019)
Orchid cattleya sp in phase seeds requires supply elements hara enough to growth and development .Adding to the confusion supply quite needs to be done to spawn orchid growing well developed .One alternative in the addition of the by doing hara fertilizing .Currently fertilizer available dipasaran had a composition of vary , so necessary testing fertilizer which appropriate to spawn orchid cattleya sp .This study attempts to get the library fertilizer leaves the best on the growth of seeds orchid cattleya sp .This research start in march to date 03-03 july 2018 in the garden experiment faculty agricultural tanjungpura pontianak university. Was used in the study design the experimental methods are random complete ( ral ) , consisting of 5 treatment and every treatment consisting of 5 deuteronomy and every unit consisting of 3 treatment plant sample the total sample obtained 75 plants .Treatment that is used is the type of fertilizer leaves where a: fertilizer super bionic , b: fertilizer bio sugih , c: fertilizer orchid booster premium , d: fertilizer top g2 , e: fertilizer green a tonic .Variable observed in this research is the addition of another long narrow leaves ( cm ) , number of leaves ( strands ) , the addition of another wide leaves ( cm ) and number of the root ( strands ) .Based on the research done it can be concluded that fertilizer a kind of green a tonic , super bionic and bio sugih can be used as a fertilizer for growth long narrow leaves , and number of leaves , seeds cattleya orchid sp .